2008
DOI: 10.1071/rd07190
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation into the dissolved oxygen levels in follicular fluid of the developing human follicle using mathematical modelling

Abstract: Oxygen levels in the follicle are likely to be critical to follicle development. However, a quantitative description of oxygen levels in the follicle is lacking. Mathematical modelling was used to predict the dissolved oxygen levels in the follicular fluid of the developing human follicle. The model predictions showed that follicular fluid dissolved oxygen levels are highly variable among follicles, due to the unique geometry of individual follicles. More generally, predictions showed that oxygen levels in fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 20 publications
3
54
0
Order By: Relevance
“…Predicted and actual measurements of oxygen concentration in antral follicles are similar to those in venous blood (Redding et al, 2008). Thus, the oxygen supply to the oocyte may only be limited at the late preantral to early antral stage and at the early preovulatory stage (Redding et al, 2007(Redding et al, , 2008. Follicle angiogenesis at these stages could be crucial for oocyte oxygen-ation and development (Van Blerkom, 2000).…”
Section: Carbohydrate Metabolism Throughout Folliculogenesismentioning
confidence: 83%
See 2 more Smart Citations
“…Predicted and actual measurements of oxygen concentration in antral follicles are similar to those in venous blood (Redding et al, 2008). Thus, the oxygen supply to the oocyte may only be limited at the late preantral to early antral stage and at the early preovulatory stage (Redding et al, 2007(Redding et al, , 2008. Follicle angiogenesis at these stages could be crucial for oocyte oxygen-ation and development (Van Blerkom, 2000).…”
Section: Carbohydrate Metabolism Throughout Folliculogenesismentioning
confidence: 83%
“…Other studies in the human (Redding et al, 2008) and bovine (Clark and Stokes, 2011) predict a sharp rise in intrafollicular oxygen with antrum formation, peaking at the end of the early antral stage before decreasing through the antral to preovulatory stages, and to finally increase around the time of ovulation. Predicted and actual measurements of oxygen concentration in antral follicles are similar to those in venous blood (Redding et al, 2008). Thus, the oxygen supply to the oocyte may only be limited at the late preantral to early antral stage and at the early preovulatory stage (Redding et al, 2007(Redding et al, , 2008.…”
Section: Carbohydrate Metabolism Throughout Folliculogenesismentioning
confidence: 87%
See 1 more Smart Citation
“…indeed. may even be the stimulus for antral formation (Redding et al 2007(Redding et al , 2008. However, previously we have reported that HIF activity is not associated with follicular growth at any stage of mouse ovarian folliculogenesis, but is evident immediately following the ovulatory signal, associated with granulosa cell luteinisation (Tam et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…The oxygen concentrations in the follicular fluid (FF) are lower in large follicles than in small follicles in cows (de Castro et al 2008), sows (Basini et al 2004) and women (Redding et al 2008). The oxygen concentration in the FF decreases with the oocyte maturation (Fischer et al 1992).…”
Section: Roles Of Hypoxic Signaling In Follicular Development and Ovumentioning
confidence: 99%